Educação e pandemia impactos e desafios - Cordeiro, Ana Paula (Editora Oficina Universitária, 2022)
The work Education and the pandemic: impacts and challenges, organized by Luciana Aparecida de Araújo and Ana Paula Cordeiro, has, among many, one feature that cannot be ignored. It was woven in times of the pandemic, caused by the Sars-Cov-2 virus. Make that your motto and face the challenge of thinking, amid the turmoil caused by this pandemic that seems to have no end. It presents important reflections relating, as the title itself informs us, education to the pandemic which is, undeniably, one of the biggest and most overwhelming that we have recorded in our history. The hypothesis that seems irrefutable is that education has been deeply upset in these times, which has already been the target of so many forms of exclusion, impoverishment by public policies, which under the guise of seeking to make it more accessible and fair for all os, since kindergarten, bends in front of the business community that sucks her in the guts.